1999
DOI: 10.1177/0265407599162009
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Attachment and Responses to Accommodative Dilemmas among Interethnic/Interracial Couples

Abstract: In the present study, partners from 103 heterosexual interethnic/interracial couples (103 men and 103 women) completed categorical measures of attachment style and continuous measures of responses to accommodative dilemmas. Consistent with hypotheses, there was a significantly higher proportion of secure over insecure individuals among both sexes. Further, the difference between secure and insecure individuals' accommodative tendencies was greater for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…On the one hand, most of the research focused on interracial couples finds no indication that interracial marriages are more difficult to maintain than intraracial marriages; Troy, Lewis-Smith, and Laurenceau (2006), for example, found no differences in the relational satisfaction, conflict style, coping, or attachment styles of individuals interracial versus intraracial relationships. Indeed, Gaines et al (1999) found high levels of a secure attachment in interracial couples. Furthermore, Leslie and Letiecq (2004) found that despite expectations to the contrary, network social support is not a particularly strong predictor of interracial marital quality.…”
Section: Predicting the Success Of Interracial Marriagementioning
confidence: 98%
See 1 more Smart Citation
“…On the one hand, most of the research focused on interracial couples finds no indication that interracial marriages are more difficult to maintain than intraracial marriages; Troy, Lewis-Smith, and Laurenceau (2006), for example, found no differences in the relational satisfaction, conflict style, coping, or attachment styles of individuals interracial versus intraracial relationships. Indeed, Gaines et al (1999) found high levels of a secure attachment in interracial couples. Furthermore, Leslie and Letiecq (2004) found that despite expectations to the contrary, network social support is not a particularly strong predictor of interracial marital quality.…”
Section: Predicting the Success Of Interracial Marriagementioning
confidence: 98%
“…Indeed, Gaines et al. () found high levels of a secure attachment in interracial couples. Furthermore, Leslie and Letiecq () found that despite expectations to the contrary, network social support is not a particularly strong predictor of interracial marital quality.…”
Section: Predicting the Success Of Interracial Marriagementioning
confidence: 99%
“…Such couples tend to report awareness of differences and curiosity about possible differences (Ham, 2003; Ting‐Toomey, 2009). Directly dealing with these issues may actually enhance intimacy (Gaines et al., 1999; Troy et al., 2006). How couples communicate about difference within the relationship and with others seems to be of prime importance (Llerena‐Quinn & Bacigalupe, 2009).…”
Section: How Can Interracial Couples Create Positive Working Marital mentioning
confidence: 99%
“…However, this mechanism can result in total isolation from support including those that the natural extended family system might afford (Falicov, 1995;Ratliff, Moon, & Bonacci, 1978). Therefore interracial couples may face ostracism and opposition not only from society at large, but also from their earliest attachment figures (Gaines et al, 1999). Whereas it is important to bring up the difficulties that interracial couples may face from individuals within and outside of their racial communities, including their families, because those difficulties could create tension within the relationship, it is also important to recognize that most interracial couples are aware of the biases against interracial marriages that exist in society and have given considerable thought to how they will approach the matter within and outside of their communities.…”
Section: Clinical Issues With Interracial Couplesmentioning
confidence: 99%